Efficacy of Tenofovir Disoproxil Fumarate in Preventing Vertical Transmission of Hepatitis B in Mothers with Chronic Hepatitis B: An Evidence-Based Case Report - Ris Raihan Felim; Irsan Hasan; Erni Juwita Nelwan (Acta Medica Indonesiana, 2024)
Background: Hepatitis B virus infection is the most common cause of chronic hepatitis. Vertical transmission is the main transmission route of this virus. Current prevention involves giving newborns immune prophylaxis within 12 hours of birth. However, there is still a failure of immunoprophylaxis, especially in cases of mothers who have a high viral load or are HBeAg positive. Tenofovir disoproxil fumarate (TDF) is the first-line treatment for chronic hepatitis B and is known to reduce perinatal HBV transmission. This study aims to determine the efficacy of TDF in preventing vertical transmission in pregnant women with chronic hepatitis B. Methods: A literature search was performed on the online databases of PubMed/MEDLINE, Embase, Scopus, Cochrane, and ScienceDirect. The inclusion criteria used were pregnant women with chronic hepatitis B and using TDF antiviral as a transmission prevention therapy with the study design used in the form of a meta-analysis, systematic review, randomized or nonrandomized controlled trial. The outcome of interest was the vertical transmission rate of hepatitis B. Results: There are two studies used with a meta-analysis study design and a nonrandomized controlled trial with a good critical review result of Validity, Importance, and Applicability. TDF significantly prevented vertical transmission of hepatitis B compared to placebo. In addition, TDF was not associated with the incidence of maternal and fetal complications. Conclusion: TDF has high effectiveness in preventing vertical transmission of hepatitis B and is safe to give to pregnant women.